PERAN STAKEHOLDERS DALAM PENGEMBANGAN DESA WISATA NONGKOSAWIT KOTA SEMARANG - Annatasya Yunita Nugroho; , Amni Zarkasyi Rahman; Kismartini Kismartini (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2022)
The city of Semarang is one of the tourist destinations for foreign and domestic tourists. Tourism villages were formed to empower the community so that they can act as direct actors in an effort to increase readiness and concern for village potential or tourist attractions in their respective villages. The development of the Nongkosawit Tourism Village can be said to be still not developing well or seems slow like other tourist villages, allegedly because the roles between the government, the community, and the private sector have not been optimal in tourism development. In this study, researchers used descriptive qualitative research methods. The results of this study are that there are five roles of stakeholders in the development of the Nongkosawit Tourism Village, namely policy creator, coordinator, facilitator, implementor, and accelerator. Stakeholders involved in the development of the Nongkosawit Tourism Village are POKDARWIS Kandang Gunung, Semarang City Culture and Tourism Office, Nongkosawit Village, Bappeda of Semarang City, Disporapar of Semarang City Public Works Service, Central Java, Universitas Negeri Semarang, Tourist, and the Nongkosawit community. The conclusion of this study is that the relationship between stakeholders is still found that is not optimal so that it hinders the development of the Nongkosawit Tourism Village. Suggestions from this research is the relationship between internal stakeholders such as the community and POKDARWIS still needs to be improved and the existing problems must be resolved immediately